ANALSIS PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH MELALUI PROGRAM SATRYA EMAS DI KABUPATEN PASURUAN - Yana Abimata Obira Kirtyawati; Arfida Boedirochminarni; Dwi Susilowati (Jurnal Ilmu Ekonomi JIE, 2019)
The Gold Satrya Program is a program that aims to provide services to improve the quality of human resources and support the development of MSMEs in Pasuruan Regency. The data used are primary data through a questionnaire distributed to 63 businessmen in Purwodadi District. The services provided are permits in the form of SIUP, PIRT and TDP. Capital related to bookkeeping as one of the conditions for obtaining capital assistance, to training in the form of skills training according to the type of business. The results of the partial test state that the variables of business licensing (0,000) and skills training (0.021) have a significant effect on the empowerment variable of MSMEs in Purwodadi District. As for the capital variable, it does not have a significant effect on the empowerment variable with a significance value of 0.540.